Enhancing the color and stress tolerance of cherry shrimp (Neocaridina davidi var. red) using astaxanthin and Bidens Pilosa. - Wei-Wei Hou; Yu-Tzi Chang; Wen-Chin Yang; Hong-Yi Gong; Yen-Ju Pan; Te-Hua Hsu; Chang-Wen Huang (PLoS ONE)
This study aimed to evaluate the effects of different concentrations of astaxanthin and Bidens Pilosa compound feed additives on the color and hypoxia tolerance of cherry shrimp (Neocaridina davidi var. red). Color parameters were assessed using CIELAB color space, and differential gene expression related to color and stress was analyzed using reverse transcription quantitative polymerase chain reaction (RT-qPCR) to understand the gene regulatory mechanisms affecting color expression and stability. Over a 56-day rearing period, the feed additives AX100 (astaxanthin 100 mg/kg) and AX100+BP (astaxanthin 100 mg/kg + B. pilosa 5 g/kg) significantly reduced the color difference values compared to the standard sample (ΔE*ab), indicating notable color boosting effects. This included a reduction in lightness (L*), a decrease in color hue angle (h*) with AX100, and an increase in redness (a*) and chroma (C*) with AX100+BP. We further designed 22 color-related gene primers, 16 of which amplified the target fragment. Six gene sets exhibited significant differences among all feed treatment groups and were correlated with color expression. After 9 hours of hypoxic stress, body color remained stable in the feed additive groups, especially in the AX100 + BP and AX200 + BP (astaxanthin 200 mg/kg + B. pilosa 5 g/kg) groups, with color differences before and after hypoxic stress remaining below the discernible threshold of the human eye, indicating optimal color stability. Additionally, the CAT gene, among the stress-related genes that successfully amplified, showed significant differences among feed treatment groups and correlated with color stability based on color difference values. In conclusion, the composite addition of 100 mg/kg astaxanthin and 5 g/kg Bidens pilosa (AX100 + BP) was identified as the most effective treatment. This formulation significantly enhanced cherry shrimp color, evidenced by improved parameters such as decreased lightness and increased redness. Moreover, AX100 + BP demonstrated superior color stability under hypoxic conditions, with ΔE*ab values remaining below the discernible threshold of the human eye, highlighting its potential for maintaining optimal color during transportation. Offering a basis for enhancing the commercial value and reducing the sale risks of cherry shrimp.